Psychometric Properties of a Cyberaggression Measure in Mexican Students - Christián Denisse Navarro-Rodríguez; Sheri Bauman; José Ángel Vera Noriega; Angel Emigdio Lagarda Lagarda (Behavioral Sciences, 2023)
Cyberaggression is an important problem today; it can affect adolescents in different ways. Therefore, reliable and valid measures are necessary to better study the phenomenon. The aim of the present study was to generate validity and reliability evidence for a Spanish-language cyberaggression scale from Garaigordobil, (2017) in a population of 1695 adolescents from northwestern Mexico (51.5% female) between 12- and 15-years-of-age. The results of this study contribute to the research and focus on cyberaggression in adolescents in Mexico. The measure used in this paper detects the different roles, including the bystander, rigorously testing the reliability and validity of the measure, providing a solid tool to evaluate cyberaggression in the Mexican context and guide evidence-based interventions and policies in educational settings.